Seasonal Patterns of Soil Respiration and Related Soil Biochemical Properties under Nitrogen Addition in Winter Wheat Field - Liang, Guopeng; Houssou, Albert A.; Wu, Huijun; Cai, Dianxiong; Wu, Xueping; Gao, Lili; Li, Jing; Wang, Bisheng; Li, Shengping (PloS one, 2015)
Understanding the changes of soil respiration under increasing N fertilizer in cropland ecosystems is crucial to accurately predicting global warming. This study explored seasonal variations of soil respiration and its controlling biochemical properties under a gradient of Nitrogen addition during two consecutive winter wheat growing seasons (2013-2015). N was applied at four different levels: 0, 120, 180 and 240 kg N ha(-1) year(-1) (denoted as N0, N12, N18 and N24, respectively). Soil respiration exhibited significant seasonal variation and was significantly affected by soil temperature with Q10 ranging from 2.04 to 2.46 and from 1.49 to 1.53 during 2013-2014 and 2014-2015 winter wheat growing season, respectively. Soil moisture had no significant effect on soil respiration during 2013-2014 winter wheat growing season but showed a significant and negative correlation with soil respiration during 2014-2015 winter wheat growing season. Soil respiration under N24 treatment was significantly higher than N0 treatment. Averaged over the two growing seasons, N12, N18 and N24 significantly increased soil respiration by 13.4, 16.4 and 25.4% compared with N0, respectively. N addition also significantly increased easily extractable glomalin-related soil protein (EEG), soil organic carbon (SOC), total N, ammonium N and nitrate N contents. In addition, soil respiration was significantly and positively correlated with β-glucosidase activity, EEG, SOC, total N, ammonium N and nitrate N contents. The results indicated that high N fertilization improved soil chemical properties, but significantly increased soil respiration.